2022
DOI: 10.3390/biomedicines10010191
|View full text |Cite
|
Sign up to set email alerts
|

Pretherapeutic Serum Albumin as an Outcome Prognosticator in Head and Neck Adenoid-Cystic Carcinoma

Abstract: Background: A head and neck adenoid-cystic carcinoma is a rare malignant tumor arising from the salivary gland tissues. The long-term survival outcome is poor due to a high risk of recurrences and distant metastasis. The identification of prognostic markers could contribute to a better risk assessment of each patient. The aim of this study is to assess the potential prognostic value of serum albumin in patients with head and neck adenoid-cystic carcinomas. Patients and Methods: This retrospective cohort study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Lastly, the two final constituents of the SI are albumin and BMI. These markers positively reflect the patient’s nutrition level from the peripheral, blood, and clinical perspectives [ 19 , 31 ]. Moreover, cancer-related systemic inflammation also results in loss of weight and cell mass, ultimately reflected by a lower BMI and decreased levels of serum albumin [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the two final constituents of the SI are albumin and BMI. These markers positively reflect the patient’s nutrition level from the peripheral, blood, and clinical perspectives [ 19 , 31 ]. Moreover, cancer-related systemic inflammation also results in loss of weight and cell mass, ultimately reflected by a lower BMI and decreased levels of serum albumin [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering albumin less than 3.5 mg/dl as hypoalbuminemia, it is found in 112 cases (36.9%). 16 Commonest site of carcinoma having anaemia varies across the studies and does not bear any correlation except bleeding history bears a certain correlation with anaemia. (13) Gynaecological cancers and urogenital cancers have the highest prevalence and this is likely due to bleeding associated with this malignancy.…”
Section: Prevalence Of Hypoalbuminemiamentioning
confidence: 99%
“…In the study by Friedl M et al, the authors performed a retrospective analysis on patients with head and neck adenoid-cystic carcinoma with available albumin levels, and they found that survival was shorter in the low-albumin group. The difference between the low- and high-albumin groups in terms of survival was significant in terms of disease-free survival, albeit not in terms of overall survival [ 4 ].…”
mentioning
confidence: 99%